Analisis Strategi Komunikasi Dakwah Kajian Islam Intensif di Yayasan Pesantren Islam Al-Falah Dago Bandung - Nurlatipah Nur; Bambang Saiful Ma’arif (UNISBA Press, 2022)
Abstract. The purpose of this paper is to get a complete picture in the analysis of the communication strategy of da'wah for intensive Islamic studies at the Al-Falah Dago Islamic boarding school foundation, Bandung. The problem that arises is how the communication strategy of da'wah in intensive Islamic studies activities at the Al-Falah Dago Islamic boarding school foundation in Bandung. This paper is the result of research at the Al-Falah Dago Islamic boarding school foundation in Bandung which has a study routine program for teachers and staff. The research method is qualitative with observation, interview, literature study and documentation techniques. As an Islamic boarding school foundation which has several units in the Bandung city area. The Al-Falah Dago Islamic Boarding School Foundation is a foundation that seeks to provide Islamic teachings regarding faith and morality so that teachers and staff do not carelessly carry out worship. Through the study program the foundation can provide knowledge to the teachers and staff who are guided by the da'i invited by the foundation. In modern times the development of da'wah has developed very rapidly. However, the da'i communication strategy carried out by the da'i was less effective, resulting in a lack of enthusiasm for teachers and staff when listening to lectures. The da'wah communication strategy in intensive Islamic studies has not been effective because the da'i did not pay much attention to the da'wah communication strategy during the study. Therefore, it is very important to pay attention to strategies when preaching so that the goals expected by the da'i are achieved. Abstrak. Maksud dari tulisan ini adalah untuk mendapatkan gambaran yang utuh dalam analisis strategi komunikasi dakwah kajian Islam intensif di yayasan pesantren Islam Al-Falah Dago Bandung. Persoalan yang mengemuka adalah bagaimana strategi komunikasi dakwah dalam kegiatan kajian Islam intensif di yayasan pesantren Islam Al-Falah Dago Bandung. Tulisan ini merupakan hasil dari penelitian di yayasan pesantren Islam Al-Falah Dago Bandung yang mempunyai program rutinan kajian untuk para guru dan staf. Metode penelitiannya yaitu kualitatif dengan teknik observasi, wawancara, studi kepustakaan dan dokumentasi. Sebagai yayasan pesantren Islam yang mempunyai beberapa unit di daerah Bandung kota. Yayasan pesantren Al-Falah Dago merupakan yayasan yang berupaya untuk memberikan ajaran Islam mengenai akidah dan ahklak supaya para guru dan staf tidak sembarangan dalam menjalankan ibadah. Melalui program kajian yayasan bisa membekali ilmu kepada pihak guru dan staf yang pandu oleh para da’i yang diundang oleh yayasan. Di zaman modern perkembangan dakwah mengalami perkembangan yang sangat pesat. Namun stretegi komunikasi dakwah yang dilakukan oleh da’i kurang efektif sehingga mengakibatkan kurangnya antusias guru dan staf saat mendengarkan ceramah. Strategi komunikasi dakwah dalam kajian Islam intensif belum efektif karena da’i tidak terlalu memperhatikan strategi komunikasi dakwah saat kajian. Oleh karena itu sangat penting memperhatikan strategi saat berdakwah supaya tujuan yang diharapkan da’i tercapai.